Pattern Analysis of Oxygen Saturation Variability in Healthy Individuals: Entropy of Pulse Oximetry Signals Carries Information about Mean Oxygen Saturation - Bhogal, Amar S.; Mani, Ali R. (Frontiers in Physiology, 2017)
Pulse oximetry is routinely used for monitoring patients’ oxygen saturation levels with little regard to the variability of this physiological variable. There are few published studies on oxygen saturation variability (OSV), with none describing the variability and its pattern in a healthy adult population. The aim of this study was to characterise the pattern of OSV using several parameters; the regularity (sample entropy analysis), the self-similarity (detrended fluctuation analysis (DFA)) and the complexity (multiscale entropy (MSE) analysis). Secondly, to determine if there were any changes that occur with age. The study population consisted of 36 individuals. The ‘young’ population consisted of 20 individuals [Mean (±1SD) age = 21.0 (±1.36 years)] and the ‘old’ population consisted of 16 individuals [Mean (±1SD) age = 50.0 (±10.4 years)]. Through DFA analysis, OSV was shown to exhibit fractal-like patterns. The sample entropy revealed the variability to be more regular than heart rate variability and respiratory rate variability. There was also a significant inverse correlation between mean oxygen saturation and sample entropy in healthy individuals. Additionally, the MSE analysis described a complex fluctuation pattern, which was reduced with age (p<0.05). These findings suggest partial “uncoupling” of the cardio-respiratory control system that occurs with ageing. Overall, this study has characterized OSV using pre-existing tools. We have showed that entropy analysis of pulse oximetry signals carries information about body oxygenation. This may have the potential to be used in clinical practice to detect differences in diseased patient subsets.